Geoelectrical and geotechnical investigation of foundation failure in and around Oroke high school, Akungba- Akoko, southwestern Nigeria - O.A, Odundun; V.I, Fagorite; E.O, Rogbitan (International Journal of Advanced Geosciences, 2020)
Engineering structures are designed and constructed with an air of lifelong expectancy. Moreover, building foundation may experience failure due to presence of concealed geologic features such as cavity and shear zones which can lead to subsurface subsidence. Hence, it is imperative, prior to building construction, to investigate the physical properties of foundation soils and determine its suitability for design and construction of building structures. In the light of this, a geoelectric survey, involving three (3) electrical dipole - dipole array and geotechnical analysis methods were carried out around a distressed building at Oroke High School, opposite Adekunle Ajasin University, Akungba Akoko to establish the cause of failure for the structures foundation via delineating the subsurface structural features. The field electrical data were plotted on log –log graph sheets and the resulting curves were interpreted qualitatively by visual inspection, and quantitatively via partial curve matching and computer iteration techniques. For the geotechnical analysis, a total of twelve (12) soil samples were taken from different locations of about 30 meters intervals, at the depth of 1.5 meters. The pseudo – section and electrical sections indicate that the subsurface is heterogeneous in geological composition. The 2D dipole- dipole resistivity and pseudo – section delineated zones having resistivity values ranging from 200 to 700ohm meter, and those approaching infinity all within a depth of 0-5 m, the resistivity values of 27 to 139ohm meter suggest the presence of clay. The geoelectric section identified three subsurface geologic layers comprising clay /sandy, clay top soil / sub grade soil, clay / sandy clay and sand weathered layer and the basement (fresh) beneath the failed segment. Additionally, prominent fractures were discovered within some areas on the pseudo-sections. The results of the laboratory tests also included those of natural moisture content, specific gravity, grain size distribution curves, Atterberg limit, compaction test and California Bearing Ratio (CBR). In conclusion, electrical resistivity method was found to be an effective measure or tool in the site characterization. The soil/rock in these zones may require reinforcement in order to enhance its bearing capacity and increase the life span of the engineering foundation.